Optyczna koherentna tomografia w obrazowaniu kąta przesączania - Drzyzga, Łukasz; Mrukwa-Kominek, Ewa; Mielniczuk, Ewa; Romaniuk, Wanda (Klinika Oczna / Acta Ophthalmologica Polonica, 2011)
Anterior segment optical coherence tomography (AS OCT), enables visualization and measurements of the anterior segment of the eye. In particular, it is a valuable tool in the imaging of the iridocorneal angle. In this paper, we reviewed parameters used for analysis of the iridocorneal angle in AS OCT and compared changes of these parameters after cataract surgery, laser iridotomy and illumination. Special attention was paid to changes of such quantitative parameters as TISA (trabecular-iris space area), AOD (angle opening distance), and ARA (angle recess area).